2003
DOI: 10.1002/lsm.10220
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of possible side effects of intra‐operative photodynamic therapy on rabbit blood vessels and nerves

Abstract: Our results have shown that mTHPC mediated intra-operative PDT used with a maximal treatment protocol (very high doses and very short drug-light intervals) has significant histological impact onto all tissue structures, but did not show any clinical symptoms in rabbits. mTHPC mediated intra-operative PDT seems to be a promising and a safe treatment option which could complement existing treatment modalities in order to improve total survival rate of tumour patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…Thus anecdotally, nerves seem to tolerate PDT well. This conclusion is supported by a recent experimental study looking at the effect of PDT with mTHPC on normal arteries and nerves (Kübler et al, 2003). This is an aspect that should be studied in further detail, as it is potentially a major attraction of PDT.…”
Section: Discussionsupporting
confidence: 62%
“…Thus anecdotally, nerves seem to tolerate PDT well. This conclusion is supported by a recent experimental study looking at the effect of PDT with mTHPC on normal arteries and nerves (Kübler et al, 2003). This is an aspect that should be studied in further detail, as it is potentially a major attraction of PDT.…”
Section: Discussionsupporting
confidence: 62%
“…This observation needs to be followed up by animal studies to explore whether this phenomenon occurs in vivo before its potential for application in the clinical setting can be determined. Importantly, in the animal studies and human cases in which peripheral nerve sparing has been reported, the PDT was applied to the nerve trunk rather than to the ganglia containing the neuronal cell bodies (Ris et al, 1996;Kubler et al, 2003;Lou et al, 2004;Betz et al, 2007). Our in vitro study indicates that neurons might survive PDT directly applied to the ganglia if an appropriate mTHPC concentration and light dose were used, enabling PDT to be applied to areas of the body rich in neuronal cell bodies such as the DRGs without killing the neurons.…”
Section: Discussionmentioning
confidence: 89%
“…This feature of nerve tissue is not accounted for in cell culture and in vivo if neurons survived a PDT insult they might still be compromised by severe damage to their blood supply. It has been shown in rabbits that some blood vessels are relatively resistant to mTHPC-mediated PDT (Kubler et al, 2003), however, in studies investigating the effect of other photosensitisers, it has been difficult to determine whether nerve function is affected by direct damage to neurons or indirect damage to the vasculature supplying the neural tissue (Dole et al, 2005;Huang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of the PDT vascular response in an animal model is complex, since the tumor overall response is a combination of the damage in cells, extracellular matrix, and vessels. The determination of the induced vascular response for different photosensitizers may improve the safety of the present PDT clinical protocols [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%